Synthesis and aqueous solution properties of multinuclear oxo-bridged vanadium(IV/V) complexes - Keramidas, Anastasios D.; Drouza, Chryssoula (My University, 2000)
Reaction of the multifunctional phenolic ligands 2,5-bis[N,N-bis(carboxymethyl)aminomethyl]hydroquinone (H6cahq), 2,2'-bis[N,N-bis(carboxymethyl)aminomethyl]-4,4'-isopropylidenedi phenol (H6capd), 2,2',2''-tris[N,N-bis(carboxymethyl)aminomethyl]-1,1,1-tris(4-hyd roxyphenyl)ethane (H9catp) and the monofunctional 2-[N,N-bis(carboxymethyl)aminomethyl]-4-carboxyphenol (H3cacp), with VOSO4 and NaVO3 affords the oxo-bridged mixed-valence vanadium(IV/V) Na6[(VO)4(μ-O)2(μ-cahq)2] · Na2SO4 · 20H2O (1), H(n)Na3-(n)[(VO)2(μ-O)(μ-cacp)2] (2), H(n)Na(3-n)[(VO)4(μ-O)2(μ-capd)2] (3), H(n)Na(9-n)[(VO)6(μ-O)3(μ3-catp)2] (4). In addition to the synthesis, we report the infrared, magnetic, optical and electrochemical properties of these complexes. The hydrolytic stability at different pH values was also investigated using visible spectroscopy. (C) 2000 Elsevier Science Inc
Keywords: Chemical analysis; Chemical reactions; Electrochemical analysis; Electrochemistry; Hydrogen-ion concentration; Phenols; Spectrophotometry; Vanadium compounds